1979
DOI: 10.1063/1.326008
|View full text |Cite
|
Sign up to set email alerts
|

Electron mobility and free-carrier absorption in GaAs: Determination of the compensation ratio

Abstract: Theoretical calculations of electron mobility and free-carrier absorption in n-type GaAs at room temperature were carried out taking into consideration all major scattering processes. It was found that satisfactory agreement between theoretical and experimental results on free-carrier absorption is obtained only when the effect of compensation is quantitatively taken into account. In conjunction with experimental studies it is shown that the electron mobility (for n≳1015 cm−3) and free-carrier absorption (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(56 citation statements)
references
References 25 publications
1
50
1
1
Order By: Relevance
“…Thus, the absorption processes can be reliably estimated by the semi-classical description assuming that the carriers are accelerated by the electric force −e F las . As a consequence, the ω −p (p ∼ 2−3) bulk behavior characteristic of the Drude-like approach 16,17 , is recovered in this two-dimensional system for this in-plane polarization configuration.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the absorption processes can be reliably estimated by the semi-classical description assuming that the carriers are accelerated by the electric force −e F las . As a consequence, the ω −p (p ∼ 2−3) bulk behavior characteristic of the Drude-like approach 16,17 , is recovered in this two-dimensional system for this in-plane polarization configuration.…”
Section: Resultsmentioning
confidence: 93%
“…This has important consequences for a BIB detector. As discussed in It has been observed that the compensation ratio, as determined based on the carrier concentration and Hall mobility within the model of Walukiewicz et al [67], is always between 10 and 90% for LPE GaAs films regardless of the majority dopant concentration.…”
Section: Compensation In Doped Lpe Gaas Filmsmentioning
confidence: 98%
“…The free electron concentration of sample 312 as a function of annealing temperature is displayed in Figure 4.6. The Hall mobility and resistivity measured after each anneal is displayed in Table 4.2, along with the compensation ratio determined from [67]. The free electron concentration and other transport properties of the sample saturate at annealing temperatures above 725 • C, with a compensation ratio of between 0.55 and 0.6.…”
Section: Neutron Transmutation Doping Of Gaasmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting Te concentrations in the films vary from 1x10 15 cm -3 to 2.1x10 16 cm -3 (Table I). Based on the measured free electron concentration and mobility we estimate the compensation 9 of the films to be between 60-70% for samples 294 and 295, and 80-90% for sample 286.…”
mentioning
confidence: 99%